Comparative Distribution of Repetitive Sequences in the Karyotypes of Xenopus tropicalis and Xenopus laevis (Anura, Pipidae) - Roco, Álvaro S. (Genes (Basel), 2021)
Xenopus laevis and its diploid relative, Xenopus tropicalis, are the most used amphibian models. Their genomes have been sequenced, and they are emerging as model organisms for research into disease mechanisms. Despite the growing knowledge on their genomes based on data obtained from massive genome sequencing, basic research on repetitive sequences in these species is lacking. This study conducted a comparative analysis of repetitive sequences in X. laevis and X. tropicalis. Genomic in situ hybridization (GISH) and fluorescence in situ hybridization (FISH) with Cot DNA of both species revealed a conserved enrichment of repetitive sequences at the ends of the chromosomes in these Xenopus species. The repeated sequences located on the short arm of chromosome 3 from X. tropicalis were not related to the sequences on the short arm of chromosomes 3L and 3S from X. laevis, although these chromosomes were homoeologous, indicating that these regions evolved independently in these species. Furthermore, all the other repetitive sequences in X. tropicalis and X. laevis may be species-specific, as they were not revealed in cross-species hybridizations. Painting experiments in X. laevis with chromosome 7 from X. tropicalis revealed shared sequences with the short arm of chromosome 3L. These regions could be related by the presence of the nucleolus organizer region (NOR) in both chromosomes, although the region revealed by chromosome painting in the short arm of chromosome 3L in X. laevis did not correspond to 18S + 28S rDNA sequences, as they did not colocalize. The identification of these repeated sequences is of interest as they provide an explanation to some problems already described in the genome assemblies of these species. Furthermore, the distribution of repetitive DNA in the genomes of X. laevis and X. tropicalis might be a valuable marker to assist us in understanding the genome evolution in a group characterized by numerous polyploidization events coupled with hybridizations.